Лучшие сочинения по русской литературе - Лазарчук Елена Николаевна (Современный литератор, 1999)
Экземпляры: (20160314) / Инвентарный номер: 34888 / Цена: / Сис.шифр: 83.3(0) / Авт.знак: Л 87 / ББК: 83.3(0)